Peran Guru PAI dalam Menanamkan Kesadaran Sosial pada Peserta Didik di SMPN 1 Bayang - Sari, Silvia Okta; Putra, Rido (Lembaga Yasin AlSys, 2025)
Social awareness is a critical component in the character formation of students and should be instilled from an early age. This study aims to describe the role of Islamic Education (PAI) teachers in educating, guiding, and directing students at SMPN 1 Bayang concerning the importance of social awareness. A qualitative approach with a phenomenological method was employed, using data collection techniques that included observation, interviews, and documentation. The findings reveal that PAI teachers play a role in three key aspects. First, the educational aspect involves teaching social values such as responsibility, honesty, tolerance, empathy, justice, and sharing, as well as delivering exemplary narratives centered on social values. Second, the guiding aspect is implemented through case studies, simulations, social activities, the creation of inclusive classroom environments, direct role modeling, and value-based social counseling grounded in Islamic principles. Third, the directing aspect is realized by encouraging student participation in social initiatives such as community service, infak on Fridays, religious activities during Ramadan, and collective extracurricular programs. These findings indicate that PAI teachers have a strategic contribution to developing students' social awareness through a holistic and practical approach within the context of secondary education.